Sociocultural Multiculturalism in New Capital of Indonesia IKN Nusantara: Academic and Student Perspectives (International Journal of Linguistics and Indigenous Culture, 2023)
The New Capital of Indonesia IKN Nusantara is a new capital city initiated by the 7th President of the Republic of Indonesia, Jokowi Widodo, which is originally a forest area that is transformed into the center of government in Penajam Paser Utara Region of East Kalimantan Province. This article aims to analyze the perspectives of academics and students at the Faculty of Cultural Sciences, Mulawarma University related to multiculturalism in the New Capital of Indonesia IKN Nusantara by using the Liker Scale theory for instance (5) Strongly Agree, (4) Agree, (3) Moderate, (2) Disagree, and (1) Strongly Disagree. The data used in this article were from 92 academic staff and students at the Faculty of Cultural Sciences, Mulawarman University. The results revealed that (1) people in East Kalimantan Province already know the diversity and coexistence with 66 respondents equal to 71.73%, (2) already understand the differences of 64 respondents equal to 69.56%, and (3) were ready to live side by side in a frame of religious tolerance where 64 respondents or the same as 69.56%. It meant that multiculturalism has been applied in East Kalimantan in terms of the academics and students in the Faculty of Cultural Sciences regarding the New Capital “IKN Nusantara”. The highlight is multiculturalism and tolerance have been implemented in East Kalimantan and multi-ethnic conflict might happen when discrimination or the local community are not accommodated properly.